The potential implementation of CIM in Malaysian manufacturing industry / Mohd Hamidi Mohd Kassim - Mohd Kassim, Mohd Hamidi (2003)
CIM commonly used abbreviation for Computer Integrated Manufacturing. It deals with the fundamental effect on manufacturing industry of integrating manufacturing activities and facilities using computers. In this report, questionnaire survey was conducted in order to gather information about the level of CIM implementation in Malaysia. From the questionnaire feedback it, can be concluded that the level of CIM implementation are still very low. Majority of the manufacturing company in Malaysia had implemented CIM partially. It is also noted that, the manufacturing company in Malaysia are also have possibility to further (fully) implement the CIM.